2010
DOI: 10.1177/0003122410388501
|View full text |Cite
|
Sign up to set email alerts
|

Have Asian American Men Achieved Labor Market Parity with White Men?

Abstract: We use the 2003 National Survey of College Graduates to investigate earnings differentials between white and Asian American men. We extend prior literature by disaggregating Asian Americans by their immigration status in relation to the U.S. educational system, and by accounting for the effects of field of study and college type. Net of the latter variables and other demographic controls, native-born Asian American men have 8 percent lower earnings than do measurably comparable white men. Our findings show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
145
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(150 citation statements)
references
References 51 publications
4
145
1
Order By: Relevance
“…For example, prior research has shown that Asian Americans are far more likely than whites to enter into science, technology, engineering, and math (STEM) fields of study and occupations (Kim & Sakamoto, 2010). The latter more consistently provide for a higher and more stable long-term income but many Americans apparently seem to find them to lead to less intrinsically rewarding jobs (Joyner, 2011).…”
mentioning
confidence: 99%
“…For example, prior research has shown that Asian Americans are far more likely than whites to enter into science, technology, engineering, and math (STEM) fields of study and occupations (Kim & Sakamoto, 2010). The latter more consistently provide for a higher and more stable long-term income but many Americans apparently seem to find them to lead to less intrinsically rewarding jobs (Joyner, 2011).…”
mentioning
confidence: 99%
“…An important question unaddressed by these papers is whether immigrants with domestic education are comparable to natives. Kim and Sakamoto (2010) fill this gap in the literature and illustrate that completing high school in the U.S. eliminates the foreign-born disadvantage for college-educated Asian men.…”
Section: Previous Researchmentioning
confidence: 86%
“…From a life course perspective, the age at which immigrants arrive in the country can have considerable effect on their subsequent integration (Kim and Sakamoto 2010;Lee and Edmonston 2011;Rumbaut 2008;Myers and Cranford 1998;Myers et al 2009). Despite variations in understanding the process, most studies, especially those drawn from studies of the 1.5 generation of immigrants, agree that immigrants who arrive at an earlier age have better adjustment outcomes than those who arrived in the country at an older age (Kim and Sakamoto 2010;Portes and Schauffler 1994).…”
Section: At Immigration: Age At Immigrationmentioning
confidence: 99%
“…Despite variations in understanding the process, most studies, especially those drawn from studies of the 1.5 generation of immigrants, agree that immigrants who arrive at an earlier age have better adjustment outcomes than those who arrived in the country at an older age (Kim and Sakamoto 2010;Portes and Schauffler 1994). Subsequently, their economic achievements are better off.…”
Section: At Immigration: Age At Immigrationmentioning
confidence: 99%